Deepfake, cinismo y diversión en la crueldad: un caso de colegiales y pornografía en Ecuador (monográfico) - Andino Veloz, Byron Pacífico (2025)
Debates about generative artificial intelligence have gained strength, its expanded uses caused astonishment and also shock to see how they led to actions that affect the conception of reality. Deepfake is a technology that creates false videos, images or audio using deep learning algorithms and that - when combined with the logic of cynicism and cruelty towards others - affects integrity and truth. The objective of the article is to critically debate the instrumental uses of artificial intelligence to create manipulated and pornographic visual content. The methodology is qualitative in nature, with bibliographic and documentary review, interviews and a case analysis: young people created more than 700 fake photos and videos, with faces of female students of different ages, from a school in Quito. The article debates how technology, youth, pornography, the logic of cynicism, the formation of networks and digital swarms are related, as well as the need for public policies in the educational field to confront ultrafakes.